Temperature, concentration, and surface modification influence the cellular uptake and the protein corona of polystyrene nanoparticles. (August 2022) - Oberländer, J.; Champanhac, C.; da Costa Marques, R.; Landfester, K.; Mailänder, V.
Abstract: The composition of the protein corona varies depending on several parameters and influences the cellular fate of the nanocarriers. Here, we investigated the influence of three key parameters (surface charge, temperature, and plasma concentration) on the formation and composition of the protein corona of polystyrene nanoparticles and ultimately on the cellular uptake of pre-coated nanoparticles. At a fixed temperature and concentration, the surface charge, and surfactant influence its composition. We observed that the composition of the corona formed at low temperatures (4°C) is different from that formed at physiological temperatures (37°C). At low plasma concentrations (up to 25%), the corona consists of more diverse proteins than at higher concentrations. Finally, we concluded that regardless of the nanoparticle formulation, the degree of uptake by model cancer and endothelial cells of the nanoparticles decreased when pre-coated at increasing temperature or plasma concentration. Statement of significance: Drug delivery through nanocarriers is an increasingly important concept in research and medicine. One problem in the application of nanocarriers in medicine is the protein corona that forms around the nanocarriers when they get in contact with protein-containing fluids. So far, several factors have been identified that influence the composition of the protein corona and thus the biological identity of the particles. However, lacking comparability remains between the studies because different concentrations or temperatures of the protein solutions are used. In this study we demonstrate how the incubation temperature or the concentration of plasma influences the protein corona and thus the cellular uptake of polystyrene nanoparticles. Graphical abstract: Image, graphical abstract